The Roman colosseum - Macdonald, Fiona (Brighton: 2010.)
Set in Rome during the period of the Roman Empire, this book discusses why the Colosseum was built and the events it was used for. Looks at raising the money to build it, preparing the site, Roman building techniques, materials and decorations. Events discussed include wild beast displays, feasts and gladiator fights